Gjerdrum ungdomsskole - (:unkn) unknown (Chalmers tekniska högskola / Institutionen för arkitektur och samhällsbyggnadsteknik, 2023)
In 2007 Kj-a won an architectural competition amongst 11 other entries. In 2009 the school was completed. This became their fourth school, all their previous schools have had a similar concept. The school is acknowledged for its connection to the landscape and its simple form. The proposal also stood out based on its organization, function, and well-arranged communication and meeting areas. The building has a unique volume with a circular courtyard in the middle. The floor plan is arranged so that the main functions are easily accessible from each wing of the building. The school is designed to be accessible to anyone, and because of its one story, the building allows for light to simmer through, to make it feel light and open. Because of its open floor plan, the school is designed to have open classrooms, which allow for an open and inviting pedagogy.
Gjerdrum School
Keywords: Detail; Facade; Wall